KONSEPSI HUKUM ISLAM TENTANG AL-RADHA’AH (MENYUSUI ANAK) - Kholil Syu’aib (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2012)
A mother, when she nursed her son, she is not only to nurse her son with breast milk but she nursed her son with compassion, pity and refinement of a mother, the child will grow in character like pity and loving kindness. Otherwise, the children who do not get the love from their mothers, they grow into children with the soul complications, which forms in their soul urges evil cruelty and revenge. The experts of pedagogy and education among developed nations have been aware of this so that the empress emperors, nursed their own children and they are not willing to hand over their children to nurses.